2018
DOI: 10.1080/13617672.2018.1450807
|View full text |Cite
|
Sign up to set email alerts
|

Possible competences to be aimed at in ethics education – Ethical competences highlighted in educational research journals

Abstract: The aim of this article is to present varieties of ethical competence that are highlighted in ethics and moral education research articles, and to discuss them in the light of competences stressed in the Swedish curriculum, understood as an example of ethics education in compulsory school. The material consists of 1,940 educational research articles published between 2000 and 2015, and the method of analysis is inductive, focusing on ethical competence. One finding is the similarity between the study's tentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 33 publications
1
14
0
1
Order By: Relevance
“…In a recent research review of the field of ethics and moral education including 1940 peer-reviewed articles, the articles were screened regarding the understanding of 'ethical competence' that emerged (Osbeck et al 2018). The concept of 'ethical competence' was sparsely used as a term, but the dimensions of ethical competence that were identified as a result of the research review are in line with an earlier study in the field, namely, the four categories identified by Rest (1986): moral sensitivity, moral judgement, moral motivation and moral implementation.…”
Section: Ethics Education In Various Studiesmentioning
confidence: 99%
“…In a recent research review of the field of ethics and moral education including 1940 peer-reviewed articles, the articles were screened regarding the understanding of 'ethical competence' that emerged (Osbeck et al 2018). The concept of 'ethical competence' was sparsely used as a term, but the dimensions of ethical competence that were identified as a result of the research review are in line with an earlier study in the field, namely, the four categories identified by Rest (1986): moral sensitivity, moral judgement, moral motivation and moral implementation.…”
Section: Ethics Education In Various Studiesmentioning
confidence: 99%
“…The failure to take this perspective or show empathy could be related to the fact that the Iranian educational system mostly focuses on preaching moral values without promoting moral reasoning (Hasani 2015) or moral sensitivity (Gholami, Kuusisto, and Tirri 2015). It appears that lack of moral sensitivity is an issue in many educational systems (see Osbeck et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of moral education concerns diversity of worldviews and values (Van der Kooij, de Ruyter, and Miedema 2013). Teaching about diversity is needed to improve moral competencies (Franken 2018;Osbeck et al 2018). As a result of the growing Muslim population in Europe, Western researchers and educators are becoming more and more interested in moral education in Islamic countries.…”
Section: Moral Conflictsmentioning
confidence: 99%
“…Another strategy for selecting a variety of ethical perspectives, for instance by using conservative, liberal, critical and postmodern voices in relation to each other (e.g., Jones, 2009), would presumably give rise to slightly different distinctions and emphases. (Jones, 2009;Osbeck, Franck, Lilja, & Sporre, 2018). By using the voices of the four established ethicists for further interpretations, the teachers' perspectives are placed in an ethical landscape.…”
Section: Discussionmentioning
confidence: 99%
“…The individualistic perspective sometimes reflects what Thornberg (2008aThornberg ( , 2008b calls an implicit values education, aiming at self-regulation and socialization. This perspective could be understood as being in line with the introductory parts of the Swedish curriculum that stress aspects of value transmission (Gardelli, 2016) and thereby can also be understood as prescribing a rather conservative values education (Jones, 2009;Osbeck et al, 2018). When comparing the competences emphasized by the teachers with the Swedish curriculum, the teachers have a broader conception of important ethical competences (see also Anderström, 2017).…”
Section: Discussionmentioning
confidence: 99%